The Other Mechanisms by Which the Rht Genes Improve the Harvest Index of Wheat - Celestin Ukozehasi; Eric S. Ober; Howard Griffiths (Plants, 2022)
Uncovering the mechanism that underlies the relationship between crop height and grain yield would potentially inform the strategies for improving wheat with optimal height. The aim of the research reported here was to identify the attributes able to produce wheat yield increases in Rht genotypes without further straw-shortening. Attention was given to examination in a controlled environment the question of the mechanistic foundation that determined the relationship between wheat height and yield in lines (Rht-B1b, Rht-D1b, Rht-B1c, Rht-D1c) compared to wild types in Mercia background. In addition to height reduction, this research revealed three other mechanisms by which the Rht genes may also improve the Harvest Index (HI) of wheat: (i) low Specific Leaf Area (SLA), (ii) increased Mean Residence Time (MRT) of Nitrogen (N), and (iii) increased grain number on spike.